Description of three new species of Gomphomastacinae (Orthoptera: Eumastacoidea) from the east of Qinghai-Tibet plateau, China - Ge, Jun-Jie; Agrippine, Yetchom Fondjo Jeanne; Xu, Sheng-Quan; Huang, Huateng (Zootaxa, 2021)
The grasshopper Subfamily Gomphomastacinae (Orthoptera: Acridoidea: Eumastacidae) is widely distributed in the Qinghai-Tibetan Plateau and Central Asia. This paper describes three new species: Ptygomastax nihilsulcus Ge, sp. nov. Phytomastax pentaspinula Ge, sp. nov. and Pentaspinula unispinula Ge, sp. nov. of the subfamily from the eastern Qinghai-Tibetan Plateau, along with an updated identification key of species of the related genera. Detail figures of the body and genitalia of the new species are also provided.